Livelihood Security Vis-a-Vis Extension Needs of the Fishers Inhabiting around Rudrasagar Lake, Tripura (Indian Journal of Extension Education, 2018)
Tripura is blessed with an important wetland i.e. ‘Rudrasagar lake, declared as National Lake No. 13 and International Lake numbered 1572 as a Ramsar site. The lake is an important source of fish production and fish biodiversity of the state. However, the lake at present is under threat from a variety of human induced changes to their hydrology. In this study, 140 fishers were selected by simple random sampling method in the vicinity of the lake, who are believed to be vulnerable as the resource base on which their livelihood depends (i.e. the Rudrasagar lake) is in peril. Livelihood security index of active fishers was found 76.21 as against the seasonal fishers (62.18). Among the active fishers, majority of them (59.26%) were placed at medium level of livelihood security index. Social security index of all the two classes were found to be highest among the livelihood security components. Environmental security as well as habitat security had a comparatively lower index value for both the classes. Most relevant extension needs of the fishers were alternative income generation and self-employment needs like initiation and development of different enterprises (Coefficient of relevance 0.88) followed by proper land use pattern in the vicinity of the lake (Coefficient of relevance 0.86) and conservation management of the lake (Coefficient of relevance 0.74). Skill development towards non-farm sector and sound availability of financial capital will motivate the fishers to diversify their livelihood to invest in other sector, expand their activities and smooth functioning of business. Making use of local knowledge in natural resource management, encouraging the use of more selective and environmentally friendly fishing methods, stimulating income diversification towards non fishing activities, stimulating the development of microenterprises and offering microfinance support to the fishers are some of the other suggestions of the study.